10. Identitas dan Kebijakan Luar Negeri: Komitmen Jepang Terhadap Penanganan Illegal Logging di Indonesia dalam Kerangka Asia Forest Partnership Tahun 2002 - 2012 - Afifah Rahmi Andini; Tri Cahyo Utomo; Sheiffi Puspapertiwi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Illegal logging in Indonesia has contributed to the increasing rate of deforestation andforest degradation at the globa level as it is also responsible for the increase of worldcarbon emissions. Considering that problem, Japan present to initiate the Asia ForestPartnership (AFP) in 2002 to combat illegal logging in Indonesia. This research aimed tofind the background of Japan’s commitment to the relief initiative to decrease illegallogging in Indonesia. In analyzing the background, this research uses ConstructivismParadigm by employing qualitative method with explanative type-analytical techniquesthrough interviews and literatures review. From this research, it can be known that theJapanese action in relation to its commitment to reduce illegal logging in Indonesia isstrongly related to the identity of Japan as a eco-centric country with high concern for theenvironment, as a result of the adoption of Shinto’s values.